Pengaruh Lingkungan Kerja, Pengawasan Atasan, Kompensasi, Dan Komitmen Terhadap Disiplin Kerja Egawai Pada Kantor Pengadilan Agama Rantauprapat - Hasibuan, Rahma Marsella (Universitas Labuhanbatu, 2021)
Discipline is a form of awareness of a person to obey or obey the rules and values or social norms that apply. Work discipline for employees is used as a reference or benchmark for the success of human resources to use all their abilities to achieve everything they want.This study aims to examine the factors that affect the work discipline of employees at the Religious Court office Rantau Prapat. These factors include work environment, supervisor supervision, compensation, and commitment. The population that will be used as a study is the Office of religious court employees rantauprapat totaling 40 people. In this study the authors took samples using probability sampling with simple random sampling technique approach. The data sources used are primary data with questionnaires and secondary data with company data. Data analysis method using multiple linear regression analysis method by performing classical assumption test in data management. The results of this study concluded that the factors of work environment, supervisor supervision, compensation, and commitment have a positive effect on the work discipline of employees at the Office of the Religious Court Rantauprapat.